Influenza vaccination among pregnant women in two hospitals in Sydney, NSW: what we can learn from women who decline vaccination - Jocelynne E McRae; Aditi Dey; Samantha Carlson; John Sinn; Peter McIntyre; Frank Beard; Kristine Macartney; Nicholas Wood (Sax Institute, 2022)
Objective: Pregnant women are recognised as being at risk of serious illness from influenza. Despite this, and longstanding national recommendations for vaccination in pregnancy, vaccine uptake remains suboptimal. This study aims to determine factors associated with women declining influenza vaccination in pregnancy. Method: We surveyed pregnant women from antenatal clinics at two Sydney hospitals as part of an evaluation of the New South Wales (NSW) Health 2017 influenza vaccination in pregnancy campaign. Factors associated with a woman's decision to decline influenza vaccination were assessed using Pearson's chi-square test and multivariable logistic regression. Results: Among 642 women surveyed, 58% self-reported influenza vaccination during pregnancy and 19% reported they had declined vaccination. Factors associated with a decision to decline vaccination included lack of a recommendation from a maternity care provider (adjusted odds ratio [aOR] 6.06; 95% confidence interval [CI] 3.50, 10.50), recommendation against vaccination (aOR 4.17; 95% CI 2.07, 8.38), having never previously been vaccinated for influenza (aOR 2.75; 95% CI 1.64, 4.59) and, among third-trimester women, not having been vaccinated for pertussis (aOR 2.55; 95% CI 1.32, 4.89). On univariate analyses, women who declined vaccination were more likely to disagree or feel uncertain about vaccine safety or effectiveness compared with women who chose to be vaccinated. Conclusion: Recommendations from maternity care providers remain key to a woman's decision to be vaccinated for influenza during pregnancy. Time should be allocated for vaccine discussions early in pregnancy as part of routine care. Continued efforts are needed to improve messaging to pregnant women on the benefits, safety and efficacy of influenza vaccination.